Proteomic identification and functional characterization of MYH9, Hsc70, and DNAJA1 as novel substrates of HDAC6 deacetylase activity. Issue 1 (15th October 2014) - Zhang, Linlin; Liu, Shanshan; Liu, Ningning; Zhang, Yong; Liu, Min; Li, Dengwen; Seto, Edward; Yao, Tso-Pang; Shui, Wenqing; Zhou, Jun
Abstract: Histone deacetylase 6 (HDAC6), a predominantly cytoplasmic protein deacetylase, participates in a wide range of cellular processes through its deacetylase activity. However, the diverse functions of HDAC6 cannot be fully elucidated with its known substrates. In an attempt to explore the substrate diversity of HDAC6, we performed quantitative proteomic analyses to monitor changes in the abundance of protein lysine acetylation in response to HDAC6 deficiency. We identified 107 proteins with elevated acetylation in the liver of HDAC6 knockout mice. Three cytoplasmic proteins, including myosin heavy chain 9 (MYH9), heat shock cognate protein 70 (Hsc70), and dnaJ homolog subfamily A member 1 (DNAJA1), were verified to interact with HDAC6. The acetylation levels of these proteins were negatively regulated by HDAC6 both in the mouse liver and in cultured cells. Functional studies reveal that HDAC6-mediated deacetylation modulates the actin-binding ability of MYH9 and the interaction between Hsc70 and DNAJA1. These findings consolidate the notion that HDAC6 serves as a critical regulator of protein acetylation with the capability of coordinating various cellular functions.